Experimental study of crushing process of the crushed stone - Akobirova Lola (E3S Web of Conferences, 2021)
Currently, crushers operating in a central impact manner have become widely used, which has several advantages over roller, cone, and cheek crushers. The present work shows the device and principle of a laboratory centrifugal vertical impact crusher for studying the process of crushing local gravel to obtain crushed stone with dimensions of 5-20 mm. The main influencing factors for the process are the average size of the incoming raw materials, the rotation speed of the crusher rotor, and the distance between the accelerator and the annular platform. The output parameter is the concentration of crushed stone with a size of 5-20 mm in the output (%). A full factor experiment N=23 was conducted, a regression equation was obtained, the adequacy of this model was proved by methods of mathematical statistics. It is determined that an increase in the size of the input raw material reduces the percentage ratio of the crushed stone output with dimensions of 5-20 mm, and an increase in the rotation speed of the crusher rotor, on the contrary, contributes to an increase in the crushed stone output. Using this equation, you can determine the degree of influence of each factor under investigation on the final result, which is necessary to optimize the process.